The Voices of EFL Student Teachers toward Task-Based Activities Model in a Collaborative Virtual Learning Environment - Agatha Lisa; Abdurrachman Faridi; Dwi Anggani Linggar Bharati; Mursid Saleh (Universitas Negeri Semarang, 2021)
The provision of social space for students to engage actively and meaningfully in the ongoing virtual teaching-learning environment is an essential part of the language classroom during the COVID-19 pandemic. Furthermore, the society of group and peers’ life creates effective learning experiences where students can learn from each other. Therefore, the current study aims to investigate the voices of student teachers towards the implementation of the task-based activities model in a collaborative virtual learning environment (VLE) over the course of a semester. To achieve this, 105 EFL students were randomly recruited from an English elective course at a private university in Yogyakarta, Indonesia. The participants worked together (both in pairs and in a group) to achieve a common goal by finishing five digital projects. In addition, qualitative data were gathered from classroom observation, interviews, documentation, and online class surveys. The results demonstrate that most participants responded positively within collaborative remote learning through task-based activities circles in terms of cooperation, time management, problem-solving, task strategies, shared decision-making, and behavior. However, some students encountered problems and suggestions were then proposed to improve the learning model in the present study. Finally, pedagogical implications were addressed and further work for educators interested in replicating the study was proposed.